Gene and function diversity-area relationships in the inflammatory bowel disease fecal and mucosal microbiome - Yu, Fubing; Song, Jiyang; Qi, Linyi; Liu, Jinghua; Yang, Yintiantian; Li, Wendy; Li, Lianwei; Ma, Zhanshan (Sam) (Frontiers in Microbiology, 2026)
The diversity-area relationship (DAR), an extension of the classic species-area relationship (SAR), provides a powerful framework for understanding how biodiversity scales across space. In this study, we applied DAR and its metagenomic counterpart (m-DAR) to investigate the spatial scaling of metagenomic genes (MGs) and metagenomic functional gene clusters (MFGCs) of seven functional databases in the gut microbiomes of individuals with inflammatory bowel disease (IBD) and healthy cohorts. Using shotgun sequencing data from 42 mucosal and 22 fecal samples from both healthy and IBD cohorts, we modeled how this MGs and MFGCs accrues with area (samples), estimating diversity scaling parameters (z), pair-wise diversity overlap (PDO), and maximal accrual diversity (MAD), which reflects the total potential diversity. We found that mucosal communities exhibited greater dissimilarity (less pair-wise diversity overlap) between individuals than fecal cowmmunities at the levels of gene richness and evenness (q = 1, 2), whereas fecal communities showed a stronger influence from dominant, abundant genes (q = 2, 3). Furthermore, healthy gut microbiomes showed greater similarity than those of IBD at the level of gene richness (q = 0), but showed greater dissimilarity at the level of abundant genes and dominant genes. Healthy gut microbiomes generally demonstrated a higher potential total diversity compared to those from IBD patients. Notably, fecal samples captured a broader range of microbial diversity than mucosal samples. Additionally, mucosal communities showed greater dissimilarity than fecal communities in almost all the MFGCs of the seven databases except ARDB, which showed the same trend as MGs. We also identified that specific functional clusters related to antibiotic resistance, such as genes for chloramphenicol and vancomycin resistance, displayed distinct scaling behaviors, suggesting their potential role in IBD pathogenesis. These findings demonstrate that the gut microbiome in IBD is not merely less diverse but is fundamentally restructured in its spatial architecture. The application of DAR provides a novel, quantitative insight to diagnose and understand this dysbiosis, moving beyond simple diversity metrics to capture the spatial diversity scaling of microbial genes and functions.